Developing Edpuzzle Application as Learning Media in Listening Descriptive Text: Penelitian - Nurfarah; Halimahtu Saddiah; Nazwa Inaya Sani T.; Sandra Sridevi Hutapea; Neni Afrida Sari Harahap (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aimed to develop Edpuzzle application as learning media in listening descriptive text. The research applied a Research and Development (R&D) design, adapting Borg and Gall’s model into six simplified stages. The data were obtained from two main sources, fifteen eighth-grade students at SMP Islam Al Ulum Terpadu Medan and one expert in English education who served as a validator. Data collection techniques included needs analysis to identify students’ needs, wants, lacks, and familiarity with the Edpuzzle Application, and an expert validation process to evaluate the product’s linguistic, process, layout, product, and content. The instruments of data collection consisted of a structured needs analysis questionnaire for students and a validation sheet for the expert. The techniques of data analysis combined quantitative and qualitative methods: students’ questionnaire responses were analyzed using percentage formulas, while expert judgments were scored on a Likert scale and described qualitatively. The findings were obtained through six steps: (1) gathering data and information from literature, previous research, and online descriptive texts; (2) conducting needs analysis which showed students’ priority on short, interactive, and culturally relevant videos; (3) designing the first draft by converting the descriptive text into video with embedded interactive questions; (4) validating the product by an expert; (5) revising the product; and (6) producing the final Edpuzzle video. Consequently, the final product is valid and suitable for classroom use, earning a score of 8.5 out of 10, which places it in the “Very Good” category.